Poetry and narrative: representation of the event poetically Poetic employment of narrative in the old Arabic criticism - Adday, Abdul Sattar Jabur (Al-Adab Journal, 2019)
How was the ancient Arabic poetry dealing with events; reality and fiction, such as battles and facts, for example? And how does the old Arabic criticism deal with poetry that narrates incidents, reports (akhbar) or stories? Did he analyzes, valuates it, or just refer to it, or neglect it altogether? These questions are the main axes of the research in it is quest to reveal the authoritarian vision of the old Arab criticism and its main tendency in dealing with this type of poetry. After wading through the procedures, these axes led to a deductive question: Are we facing a lack of the ancient Arab poetic forms of the event, or a lack of the critical and rhetorical vision of these forms, their classification, analysis of their methods and methods? This is what the research concluded by answering.